Factors associated with malnutrition in children under 5 years of age in the El Baboso community - Bustos Villarreal, Mónica Alexandra (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This study examines the factors associated with malnutrition in children under five years of age in the community of El Baboso, Ecuador. The objective was to identify and relate socioeconomic, cultural, and health service access factors with the prevalence of child malnutrition in this vulnerable population. A mixed-methods research design was used, combining qualitative and quantitative approaches, with a sample of 20 children and 16 parents. The results revealed that 80 % of the children were underweight, 75 % of the caregivers had no formal education, and 90 % of the children did not receive exclusive breastfeeding during the first six months. Additionally, irregular access to health check-ups and a lack of nutritional knowledge were significant factors. It is concluded that implementing educational strategies and improving access to health services is essential to address child malnutrition in this community.